2012
DOI: 10.2136/sssaj2011.0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Content on Prediction of Organic Carbon and pH Using Visible and Near‐Infrared Spectroscopy

Abstract: This study was undertaken to investigate the effect of moisture content (MC) on the prediction accuracy of soil organic C (SOC) and pH of soils collected from Turkey and the United Kingdom using a fiber-type visible and near infrared (Vis-NIR) spectrophotometer. The diffuse reflectance spectra of 270 soil samples were measured under six gravimetric MC levels of 0, 5,10,15, 20, and 25%. Partial least squares (PLS) regression analyses with full cross-validation were performed to establish models for SOC and pH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 33 publications
7
27
0
Order By: Relevance
“…Mouazen et al (2006) found that variable soil MC decreased the predictive accuracies of several soil properties, including total C and pH. Morgan et al (2009) arrived at the same conclusion for SOC and inorganic C. Likewise, Tekin et al (2012), using the same data set as that of the current study, reported significantly improved results for prediction of SOC using dry soil samples, as compared to wet ones. These authors concluded that MC significantly affects the predictive performance of both SOC and pH, although this effect was found to be greater for the former than for the latter.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Mouazen et al (2006) found that variable soil MC decreased the predictive accuracies of several soil properties, including total C and pH. Morgan et al (2009) arrived at the same conclusion for SOC and inorganic C. Likewise, Tekin et al (2012), using the same data set as that of the current study, reported significantly improved results for prediction of SOC using dry soil samples, as compared to wet ones. These authors concluded that MC significantly affects the predictive performance of both SOC and pH, although this effect was found to be greater for the former than for the latter.…”
Section: Introductionsupporting
confidence: 71%
“…Many researchers have successfully measured soil organic carbon (SOC) using vis-NIR spectroscopy (Mouazen et al, 2007;Gomez et al, 2008;Vasquez et al, 2008;Leone et al, 2012;Tekin et al, 2012). A comprehensive analysis of the literature was carried out by Stenberg et al (2010), confirming the possibility of successful measurement of SOC with vis-NIR, which was attributed to the direct spectral response of C in the NIR range.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was obvious that the performance of OC and CC models was better than that of pH model, which could be attributed to the direct spectral response in the NIR spectral range mainly Stenberg et al, 2010). The better performance of ANN-OC model, as compared to the corresponding PLSR-models might be attributed to a non-linear behavior documented for OC Stenberg, 2010;Tekin et al, 2012), which seemed to be overcome by the nature of ANN, in solving non-linear problems. However, the reason why ANN provided a better performance for OC and pH (showing no non-linear behaviour), as compared to PLSR was not clear.…”
Section: Model Performance In Cross-validationmentioning
confidence: 95%
“…As MC increases, the reflectance generally decreases nonlinearly and independent of soil type [9,10]. Therefore, most studies have demonstrated that dried soil samples are preferable for modeling of soil properties [11,12]. Unfortunately, soils may significantly vary in moisture in field conditions.…”
Section: Introductionmentioning
confidence: 99%